An ankle-foot prosthesis: A preliminary design and dynamic model - Ferreira, César (2018)
There are more than one million people, each year, that will suffer a lower limb amputation. This condition occurs as a result of a wide range of diseases: diabetes, trauma or malignant tumors. An amputation means disability and a poor quality of life. The major challenge in the development of a prosthesis lies in restoring the missing human function, i.e. locomotion while maintaining the biomechanical requirements of the ankle joint. Thus, this work addresses the field of the artificial devices that replace the ankle-foot. The goal of this work is to sketch a 3D model of a transtibial prosthesis, and to find and implement a dynamic model of human ankle joint motion, in order to be used in a future control system strategy. Thereby, this work represents the first steps towards the development of a transtibial prosthesis.